Loan guarantees and the internationalisation of Indian firms - Sunil Mani (University of Athens, Department of Economics, International Economics and Development Laboratory (IEDL), 2026)
This paper analyses the role of loan guarantees in supporting the internationalisation of Indian firms through outward foreign direct investment (OFDI) since the mid-2000s. Despite a persistent domestic savings-investment gap and recurrent current account deficits, Indian OFDI has expanded significantly, raising questions about its underlying financing mechanisms. The paper argues that regulatory liberalisation and the growing use of loan guarantees have been central to this expansion. Using balance-of-payments analysis and a stylised framework that distinguishes between private and guaranteed financing channels, the study documents a shift in OFDI financing from equity dominance towards a more diversified structure that includes reinvested earnings, intercompany loans, external commercial borrowings, and guaranteed debt. While guarantee issuance has increased markedly, invocation rates remain low, indicating that guarantees primarily serve as credit-enhancement tools rather than realised fiscal liabilities. The paper concludes that India's predominantly private-risk approach has enabled corporate internationalisation while limiting direct sovereign exposure, but also highlights the need for improved transparency and risk monitoring as guarantee volumes continue to rise.
Keywords: F21; F23; H81; G28; F34; 330; loan guarantees; outward FDI; India; corporate internationalisation; financial commitments; policy reforms